Concrete flat roof defects in equatorial climates - Mohd Sarman, Asmawan; Mohd Nawi, Mohd Nasrun; Che-Ani, Adi Irfan; Mazlan, Elis Mardzianah (Innovative Research Publications, 2015)
In recent year, many building in Malaysia have designed for a concrete flat roof rather than traditional pitched roof.There are also buildings that incorporate design slope roofs and flat roofs that keep facility equipment in the flat roof area. However due to hot and humid condition throughout the year in equatorial climate, surface-related defects, damage to the waterproofing membrane and cracks in the roof parapet wall are the common defects of roof construction that require frequent maintenance. This paper seeks to review the common defects of concrete flat roof construction in institutions of higher education buildings in equatorial climates. The research reported was carried out by the building inspection and analysis of 23 case study buildings. Surface profile and the slope of the roof, rainwater drainage, parapet wall and the waterproofing membrane inspected and analyzed. The findings of the inspection indicated that the concrete flat roof slope should be appropriate to the size of a roof and parapet wall dislocation failure is dependent on whether the ends are hinged or fixed. Failure usually leads to tearing of the waterproofing membrane. Proper surface workmanship, modification to the roof parapet wall design and to the selection of construction materials is suggested. The modes of failure and proposed modification will be of interest to designers and those responsible for the maintenance of flat-roofed buildings in equatorial climates.